General Principles of Law as a Source of International Law Between Jurisprudential Debate and International Jurisprudence - Oualhi, Mokhtar (Journal of Legal Studies and Researches, 2024)
The general principles of law are an expression of some common principles in national legal systems. Despite the jurisprudential disagreement about their existence and lack of independence as a source of international law, their application by the international judge, or arbitration was not limited to traditional fields, but rather its application extended to other new fields that became the purview of international law.